Poliandri Sebuah Refleksi Ajaran Bhakti dan Śraddhā dalam Kakawin Kreṣṇā Pancawiwāha - Wikandina Putri, Ni Made; Sudewa, I Ketut; Udayana, I Nyoman (Jayapangus Press, 2025)
Kakawin Kreṣṇā Pancawiwāha tells the story of Dewi Kresna's marriage to Panca Pandawa, which is interesting to study because the concept of marriage in this text has shifted. The marriage that is supposed to be between a man and a woman is told differently in this text, where a woman marries five men at the same time, known as polyandry. The polyandrous marriage narrated in the Kakawin Kreṣṇā Pancawiwāha text is actually not merely the main purpose, but a symbolic one that has meaning in it. The purpose of this paper is to reveal the symbolic meanings of polyandry that have relevance to Hindu religious teachings. This research is an analytical descriptive research with a textual approach that uses the text of Kakawin Kreṣṇā Pancawiwāha as the main data source. The method used in the data collection stage is literature study with translation, listening, and note-taking techniques. In the analysis stage, the analytical descriptive method was used, assisted by interpretative techniques based on the working principles of semiotic theory. The result found is that the phenomenon of polyandry in the Kakawin Kreṣṇā Pancawiwāha text is a symbol that contains religious philosophical values for Hindus to reflect the teachings of Bhakti (devotion) and Śraddhā (belief). The implementation of the teachings of Bhakti (devotion) is realized by the attitude of Satya Laksana (loyal to the righteous actions) to Guru Rupaka (parents) as a reflection of the teachings of Guru Bhakti. Symbolic polyandry as a concept of Śraddhā, is realized by the reflection of the teachings of Karmaphala Sraddha (belief in the existence of karma) which has a reciprocal relationship with Punarbhawa Sraddha (belief in the existence of repeated births). The mythology found states that polyandry is an existence of life that has implications for the improvement of Bhakti and Śraddhā.